2021
DOI: 10.1016/j.jmgm.2021.107999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-cancer and anti-covid-19 properties of cationic pentapeptide Glu-Gln-Arg-Pro-Arg, from rice bran protein and its d-isomer analogs through molecular docking simulations

Abstract: Bioactive peptides derived from food proteins are becoming increasingly popular due to the growing awareness of their health-promoting properties. The structure and mechanism of anti-cancer action of pentapeptide Glu-Gln-Arg-Pro-Arg (EQRPR) derived from a rice bran protein are not known. Theoretical and experimental methods were employed to fill this gap. The conformation analysis of the EQRPR pentapeptide was performed first and the obtained lowest energy conformer was optimized. The experimental structural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Recently, RPP is rapidly rising as a new food resource because of its functions of low sensitization, antioxidant, immune regulation, maintenance of intestinal ecology, antihypertensive, anticancer, anti-inflammatory, and prevention of COVID-19. In fact, our group had industrialized the broken rice produced in the rice processing process to obtain RPP-related products and has also been marketed with the output value of $3 million in 2021. Thus, it is of great significance to evaluate the effects of RPP on colitis and explore the possible mechanisms for the development of RPP-based functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RPP is rapidly rising as a new food resource because of its functions of low sensitization, antioxidant, immune regulation, maintenance of intestinal ecology, antihypertensive, anticancer, anti-inflammatory, and prevention of COVID-19. In fact, our group had industrialized the broken rice produced in the rice processing process to obtain RPP-related products and has also been marketed with the output value of $3 million in 2021. Thus, it is of great significance to evaluate the effects of RPP on colitis and explore the possible mechanisms for the development of RPP-based functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…The revealed interacting sites and distances are as follows: DG4 and 1,4-Bis(2-chloro-4-nitrophenyl)piperazine molecule have a pi-alkyl interaction with lengths of 4.89 Å; DA6 and 1,4-Bis(2-chloro-4-nitrophenyl)piperazine molecule have a hydrogen bond interaction with lengths of 1.92 Å. The 3D interaction scheme of the ligand and target DNA is shown in Fig 2 . In previous studies on cationic pentapeptide (Glu-Gln-Arg-Pro-Arg) and DNA interaction [29] and on vanillin-derived imine compound and DNA interactions [30], ligands were found to interact with DNA through DG4 nucleic acid. In the case of the molecular docking study between Val-Met dipeptide and DNA by Celik et al, [28] it was also found that the ligand made hydrogen bonds with DG4.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…A pentapeptide recently isolated from rice bran, EQRPR, has demonstrated antiproliferative effects against colon, lung, breast and liver cancer lines [51]. In addition, an in silico study revealed that the same pentapeptide is able to strongly interact with integrins, which is important for anticancer effects [190]. RPI has been reported to induce apoptosis in human breast carcinoma and myeloma cell lines through induction of p21 and inhibition of CDK4 and cyclin D1 activities [191].…”
Section: Cancermentioning
confidence: 99%